Pengendalian Hama Terpadu Tanaman Hortikultura pada Kelompok Tani Lokon di Kelurahan Kakaskasen II, Kecamatan Tomohon Utara: Integrated Pest Management of Horticultural Crops in the Lokon Farmer Group in Kakaskasen II Village, North Tomohon District (Tumou Tou: Jurnal Pengabdian Masyarakat, 2026)
The main problem in increasing the productivity of horticultural crops in Tomohon City is pest and disease attacks that can cause losses for farmers.  As a sustainable alternative, the Integrated Pest Management (IPM) approach is an effective solution in suppressing pest attacks without causing negative impacts on the environment.  The Cluster 2 Community Partnership Program (PKM_K2) was carried out with the following objectives: (i) to improve farmers' knowledge and skills in the application of Integrated Pest Management (IPM) in horticultural crops and (ii) to reduce the inappropriate use of chemical pesticides and replace them with more sustainable pest control methods.  The PKM_K2 activities were carried out in Kakaskasen II Village, North Tomohon District.  Activities included PHT extension on horticultural crops for the Lokon Farmer Group. Farmers were introduced to the basic concepts of PHT and pest management strategies that combine various compatible and environmentally friendly control methods.  To understand the farmers' level of knowledge of PHT, pre-tests and post-tests were conducted.  The direct result of this activity was an increase in the capacity of individual farmers, particularly in PHT. In addition, changes were observed in the patterns of social interaction among group members.  This phenomenon shows that a participatory approach can strengthen the independence of farmer groups in making evidence-based decisions.  Thus, this PKM activity not only increased individual knowledge but also strengthened the institutional capacity of farmer groups to manage their agricultural ecosystems more wisely.  The results of this activity can be published in the National Journal of Community Service.